Orthodontic Consideration in Pierre Robin Sequence Patient: a Case Report (Bangladesh Journal of Medical Science, 2026)
The Pierre Robin sequence (PRS) is a rare condition that affects 1 in 20,000 to 1 in 8,500 people. In this condition, it is not always possible for the mandible to attain its normal size, shape, and orientation. Several cephalometric studies have reported the distinctive lower jaw morphology of PRS, with a small ramus of the mandible and a steep mandibular plane. This case report will discuss a female patient diagnosed with PRS and found to have a retrognathic mandible with teeth crowding and deep bite. The patient had a convex profile, obtuse nasolabial angle, deep mentolabial sulcus, and recessive chin. Dental analysis revealed a deep bite with Angle’s Class II molar relationship. Cephalometric examination showed a class II skeletal pattern due to a retruded mandible and hyper-divergent mandibular plane. The patient was treated with a pre-adjusted edgewise orthodontic fixed appliance, cross-elastic, bonding button, and GIC to correct a crossbite, then mandibular surgical advancement with genioplasty. After a surgical recovery period of two weeks, the patient was seen in the postsurgical orthodontics department for a total of two months. After the treatment, the patient had achieved good functional occlusion, characterized by normal overjet, overbite, and adequate intercuspation, class I molars and canines relation on both sides of the mouth, nearly coincident midlines, and normal proclination of mandibular and maxillary incisors. Cephalometric measurements showed maxillary clockwise rotation and mandibular anticlockwise rotation and advancement, both of which contributed to an improved facial profile, which led to the elimination of vertical skeletal excess and corrected the recessive chin.BJMS, Vol. 25 No. 02 April’26 Page: 666-675